1999
DOI: 10.1038/4758
|View full text |Cite
|
Sign up to set email alerts
|

Human fibroblast growth factor receptor 1 is a co-receptor for infection by adeno-associated virus 2

Abstract: Adeno-associated virus 2 (AAV)-based vectors have gained attention as a potentially useful alternative to the more commonly used retroviral and adenoviral vectors for human gene therapy. Although AAV uses the ubiquitously expressed cell surface heparan sulfate proteoglycan (HSPG) as a receptor, the transduction efficiency of AAV vectors varies greatly in different cells and tissues in vitro and in vivo. We demonstrate here that cell surface expression of HSPG alone is insufficient for AAV infection, and that A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
418
1
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 477 publications
(431 citation statements)
references
References 37 publications
9
418
1
3
Order By: Relevance
“…Expression of hTERTC27 and EGFP in human glioblastoma U87-MG cells, respectively, infected with rAAV-hTERTC27 and rAAV-EGFP As AAV infection requires the presence of heparan sulfate proteoglycan and human fibroblast growth factor 1 as a co-receptor, 18 we first tested whether the packaged rAAVhTERTC27 and rAAV-EGFP can successfully infect the human glioblastoma U87-MG cells in vitro. The U87-MG cell line was chosen in this study, because it is one of the most tumorigenic glioblastoma cell lines identified to date.…”
Section: Resultsmentioning
confidence: 99%
“…Expression of hTERTC27 and EGFP in human glioblastoma U87-MG cells, respectively, infected with rAAV-hTERTC27 and rAAV-EGFP As AAV infection requires the presence of heparan sulfate proteoglycan and human fibroblast growth factor 1 as a co-receptor, 18 we first tested whether the packaged rAAVhTERTC27 and rAAV-EGFP can successfully infect the human glioblastoma U87-MG cells in vitro. The U87-MG cell line was chosen in this study, because it is one of the most tumorigenic glioblastoma cell lines identified to date.…”
Section: Resultsmentioning
confidence: 99%
“…21 AAV2 is known to enter cells through the heparin sulphate proteoglycan receptor, fibroblast growth factor receptor 1 and the integrin receptors aVb1 and aVb5. [44][45][46][47] A laminin receptor has also been implicated for AAV2 cell entry. 48 AAV6 can also bind to heparin sulphate proteoglycan receptors, 49,50 but unlike AAV2, AAV6 is not inhibited by soluble heparin.…”
Section: Discussionmentioning
confidence: 99%
“…Two coreceptors for AAV2 have thus far been identified. These include aVb5 integrin 50 and fibroblast growth 51 The level of aVb5 integrin expression can significantly influence the efficiency of rAAV2 transduction in certain cell types; however, its functions as a coreceptor has been debated. 52,53 Nonetheless, inhibition of aVb5 integrin with blocking antibodies can prevent internalization of bound rAAV2 on the surface of HeLa cells.…”
Section: Aav Attachment Receptors and Coreceptorsmentioning
confidence: 99%